Find the sum of first 10 terms of the sequence
{ 7 , 7 7 , 7 7 7 , 7 7 7 7 , … , 7 7 7 7 7 7 7 7 7 7 }
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please make the first step more clear
Divide each term by 7, the terms are then: 1, 11, 111.... 1,111,111,111). The first 9 terms will add up to 123456789 (since 9 of the terms have a 1's digit, 8 a ten's digit, etc.). The last term is merely 10 1's. Add those two numbers and you get 1234567900. Multiply by 7 (that we initially divided the terms by) to get 8641975300.
7(1+11+111.................................................1111111111)
9 7 (9)(1+11+111+1111..............................................10 terms)
9 7 (9+99+999+9999..............................10 terms)
9 7 ([10-1]+[100-1]+[1000-1]................................10 terms)
Now Applying G.P. Formula and simplifying
=86419753000
YEs,,, but see i also did the same way.. i needed Calculator for evaluating the GP.
It took alot of time and I also makes mistakes.
Bus Kuch kar raha huin
Easy ques with lengthy calculations
Problem Loading...
Note Loading...
Set Loading...
S = 7 + 7 7 + 7 7 7 + . . . + 7 7 7 7 7 7 7 7 7 7 = 7 ( 1 1 + 1 2 1 + 1 1 3 1 + . . . + 1 1 1 1 1 1 1 1 1 1 0 1 ) = n = 0 ∑ 9 7 ( 1 0 − n ) 1 0 n + 1 = 7 n = 0 ∑ 9 ( 1 0 n + 2 − n 1 0 n + 1 ) = 7 0 0 n = 0 ∑ 9 1 0 n − 7 0 n = 1 ∑ 9 n 1 0 n = 7 0 0 ⋅ 1 0 − 1 1 0 1 0 − 1 − 7 0 ⋅ 9 8 7 6 5 4 3 2 1 0 = 7 0 0 ⋅ 1 , 1 1 1 , 1 1 1 , 1 1 1 − 6 9 1 , 3 5 8 , 0 2 4 , 7 0 0 = 7 7 7 , 7 7 7 , 7 7 7 , 7 0 0 − 6 9 1 , 3 5 8 , 0 2 4 , 7 0 0 = 8 6 , 4 1 9 , 7 5 3 , 0 0 0 See note.
Note:
S 1 1 0 S 1 ( 1 − 1 0 ) S 1 − 9 S 1 ⟹ S 1 = n = 1 ∑ 9 n 1 0 n = 1 0 + 2 ( 1 0 2 ) + 3 ( 1 0 3 ) + . . . + 9 ( 1 0 9 ) = 1 0 2 + 2 ( 1 0 3 ) + 3 ( 1 0 4 ) + . . . + 9 ( 1 0 1 0 ) = 1 0 + 1 0 2 + 1 0 3 + . . . + 1 0 9 − 9 ( 1 0 1 0 ) = 1 0 ⋅ 1 0 − 1 1 0 9 − 1 − 9 ( 1 0 1 0 ) = 9 1 0 1 0 − 1 0 − 8 1 ( 1 0 1 0 ) = 8 1 8 × 1 0 1 1 − 1 0 = 9 8 7 6 5 4 3 2 1 0